“A very first clue on the subject”: A focus group study on users’ perspectives on German plain language summaries of psychological meta-analyses - Claudia Breuer; Marlene Stoll; Gesa Benz; Mark Jonas; Martin Kerwer; Anita Chasiotis (PLoS ONE, 2026)
Background Plain Language Summaries (PLSs) are textual summaries of scientific studies that are targeted at lay audiences. PLSs of psychological meta-analyses may benefit laypeople interested in psychological research, psychological practitioners and science communicators. This study explored the perspective of these three user groups on German PLSs of psychological meta-analyses. We wanted to understand the aims and benefits of reading psychological PLSs form their perspective, and how these PLSs should be designed to be useful to them. Methods We conducted four focus group interviews in total. Two focus groups comprised 15 laypeople in sum, one focus group interview comprised six practitioners, and one focus group comprised five science communicators. Interview transcripts were analyzed using content analysis according to Kuckartz and Rädiker. We used main categories for PLS aims and characteristics from a previously developed framework model to classify the content. Results All user groups appreciated the PLSs as a first insight into a broader subject. Additionally, laypeople primarily intended to use the PLSs to gain knowledge, comprehend psychological research and make informed decisions. Science communicators considered the PLSs mainly as a starting point for in-depth investigation of certain topics, while psychological practitioners regarded them rather as good educational material for clients or patients. Participants across all groups valued plain language, clear structure and short length of PLSs as well as reporting of conflicts of interest related to the presented research. Suggestions for improving the design included a general explanation of technical terms in the form of a glossary, as well as presenting the key message at the beginning. Conclusions The PLSs of psychological meta-analyses investigated in this study have the potential to improve the accessibility of psychological scientific knowledge and provide an attractive first insight into a more extensive subject. The user groups’ thoughts and ideas for improvement were implemented in the further development of the PLSs that are published by the Leibniz Institute for Psychology (ZPID).